On Some Bicomplex Hartley Transformations - Halici, Serpil; Curuk, Sule (Communications in Mathematics and Applications, 2022)
In this study, we have defined Hartley transforms for functions of bicomplex variables by using some known integral transformations, and then we examined the properties of these transformations.